Symbolic Transformation and Cultural Islamization of the Kembar Mayang Ritual: A Case Study of the Javanese Diaspora in Aek Hitetoras, North Sumatra - Manopo, Siti Hadijah; Arifinsyah, Arifinsyah (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
This article examines the symbolic transformation and cultural Islamization of the Kembar Mayang ritual among the Javanese diaspora community in Aek Hitetoras, North Sumatra. Drawing on a qualitative case study approach, the research is grounded in the anthropology of religion and based on in-depth interviews, participant observation, and analysis of documentary materials. Findings reveal that Kembar Mayang, once rooted in ancestral cosmology and mystical practice, has been reinterpreted through deliberate negotiation and adaptation. Traditional elements such as offerings and incantations have largely been replaced by Islamic prayers and Qur’anic recitation, reflecting the community’s commitment to religious orthodoxy while sustaining collective identity and social cohesion. The adaptation process has been incremental and dialogical, involving pragmatic adjustments in ritual materials and the creative use of digital media for documentation and intergenerational transmission. Contestation between cultural and religious perspectives has generated both tension and innovation, ultimately enabling the ritual to endure as a meaningful expression of gratitude, harmony, and heritage. The study contributes to broader debates in the anthropology of religion and diaspora studies, illustrating how local traditions are dynamically negotiated and renewed through cultural ijtihad, recontextualization, and digital innovation. Practical implications highlight the importance of inclusive dialogue, intergenerational education, and flexible preservation strategies for sustaining tradition within plural and rapidly changing societies.